2021
DOI: 10.1016/j.ijadhadh.2021.102891
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of interface failure behaviour for brittle adhesive using the three-point bending test

Abstract: ARTICLEINFO AB STRACT Adhesive failure Threepo int bending test Coupled criteri on Macro-element lnterfacial pr oper ties In the framework of the adhesive bonding, the assessment of interfacial properties has an essential role in determining the adhesive joints' global responses. Various surface preparations are available for each type of metallic substrate. There are plency of tests widely used for mechanical characterisation to determine the ad hesive properties and few tests to assess interfacial properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…Finally, the relation between Fe and Sc is constructed (see Figure 11), as previously described by Birro et al (2021). l 13 l Thus, the result obtained for the abraded substrate is in agreement with the typical curve obtained via pure chemical treatment.…”
Section: Three-point Bending Test Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…Finally, the relation between Fe and Sc is constructed (see Figure 11), as previously described by Birro et al (2021). l 13 l Thus, the result obtained for the abraded substrate is in agreement with the typical curve obtained via pure chemical treatment.…”
Section: Three-point Bending Test Resultssupporting
confidence: 68%
“…Nevertheless, a düferent failure mechanism is obtained during the crack propagation -interfacial failure propagation for a low rough ness instead of an interphasial failure propagation for higher roughness. Therefore, a new fracture propagation mechanism is only reached when a low F e is obtained experimentally, as previously constated by Birro et al (2021). [I 4 l Thus, the experimental and statistical studies reveal that roughness can directly impact the critical length of failure initiation as well as the mechanism of fracture propagation when a low roughness is reached, even though ail failure initiations are adhesive and independent in terms of roughness com prised from 58� R a �2120 nm.…”
Section: Statistical Analysis Of Failure Initiation Mechanism -Weibul...supporting
confidence: 60%
See 2 more Smart Citations
“…The porous samples made from ABS material used within the research showed mostly brittle behavior. Some of them, including the R_57 in Figure 10, showed a sudden drop in applied force after elastic deformation, which can be connected with the theory of failure propagation [57]. Since the cellular structures were studied within the research, it can be said that the type of failure propagation (fast or slow, along the cell boundaries or through the pores, smooth or stepwise, etc.)…”
Section: Energy Absorption and Ductility Assesmentmentioning
confidence: 75%